Impacts of electronic monitoring on the community life: blessing or disguise?. Issue 3 (5th February 2021) - Vitálišová, Katarína; Borseková, Kamila; Vanˇová, Anna; Koróny, Samuel
Abstract : Purpose: The purpose of this paper is to identify and evaluate critically the impacts associated with the implementation of electronic monitoring (EM) of accused and convicted persons on society based on the foreign experience and compare these findings with the original research results on EM in the Slovak Republic. Design/methodology/approach: This paper elaborates the secondary data of previous researches in Scotland, Sweden and Florida in the USA. Secondary research is based on in-depth analysis of articles, reports and studies searched via database of Google, Scopus and Science Direct. Based on the studies processed by a causal and qualitative analysis, the authors identify the benefits and risks of EM influencing community life in Europe and the USA. The additional sources of secondary data are the Statistical Yearbook of Ministry of Justice of Slovak Republic, the content of the original law (including relevant amendments) that introduced EM into the Slovak criminal justice system and data on the application of EM in Slovakia provided by the Ministry of Justice. Subsequently, this paper presents the original research findings about the EM implementation in the Slovak Republic. The primary data were conducted via interviews with the representatives of Ministry of Justice, and through the national survey of opinions of judges, probation and mediation officers. The authors used the descriptive statistics and the statistical deduction methods. Findings: The key finding of the paper is that there is a very narrow border between EM as blessing and disguise for community involved. Setting proper measures to protect the community, targeted communication and support with attendance of professionals (e.g. mediator and psychologist) for community members might help to avoid possible risks and support the benefits related with EM implementation, namely, social and economic inclusion of offenders, maintaining family and community tights, reducing recidivism or protection of sensitive sites. Practical implications: To support the acceptation of EM by local community, the authors recommend to perceive sensitively community involvement and consider potential risks related with EM implementation; to suggest the proper measures to protect the community; and to develop better or targeted communication oriented towards increasing awareness or establishment supporting groups with attendance of professionals (e.g. mediator and psychologist) that might help to avoid possible risks and support the benefits related with EM implementation. Originality/value: This paper compares experience with EM based on the secondary data of previous researches in Scotland, Sweden and Florida in the USA. Subsequently, it presents the unique data about the implementation of EM in the Slovak Republic. The topic of EM is still vastly underrated in the literature, and there is a lack of empirical data, so this paper as a combination of case studies and original research could be very helpful in the efficient implementation of EM and setting the proper measures.